Egyptian cults and sanctuaries on Delos - Brun-Kyriakidis, Hélène (Epitome, 2021)
Renowned to this day for its Sanctuary of Apollo, the island of Delos was a flourishing trading port in antiquity that drew both Greeks and foreigners to its shores for commercial purposes. Many exotic deities some hailing from the east and others, introduced by the Italian community, from the west were worshipped on the island. Among these foreign divinities, the Egyptian gods figured prominently, and their first appearance can be dated to the 3rd century BC. The spread of Egyptian-Greek cults beyond the Nile Valley favoured the worship of the goddess Isis. While the goddess was the object of great devotion on Delos as elsewhere, it was actually the god Sarapis who was at the centre of a pantheon forming a triad with Isis and Anubis, joined by Harpocrates, Ammon and Osiris.